Automated artefacts detection and removal in remote sensing optical imageries - Guancia, Dustin Joseph Co (Nanyang Technological University, 2021)
Remote Sensing is the process of gathering information, recording, or observing objects or events from a far away distance, without contacting it physically. Remote sensing has increasingly become more popular due to its applicability in many different fields such as geography and military. However, the output images of the remote sensors have a poor quality, or sometimes contains artefacts. This will hinder the data processing from the captured images. This project aims to study and develop different methods to detect and remove artefacts in the satellite images. This project also explores the MATLAB Image Processing Toolbox and the corresponding functions to aid with the objective of the project. Several MATLAB image processing functions will be used to produce MATLAB algorithms for artefacts detection, followed by the removal. The different methods will then be compared and analyzed based on their efficiency to carry out the tasks.